2023
DOI: 10.1093/stcltm/szad031
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Brain-Derived Ischemia-Induced Multipotent Stem Cells Ameliorates Neurological Dysfunction in Mice After Stroke

Abstract: We recently demonstrated that injury/ischemia-induced multipotent stem cells (iSCs) develop within post-stroke human brains. Because iSCs are stem cells induced under pathological conditions, such as ischemic stroke, the use of human brain-derived iSCs (h-iSCs) may represent a novel therapy for stroke patients. We performed a preclinical study by transplanting h-iSCs transcranially into post-stroke mouse brains 6 weeks after middle cerebral artery occlusion (MCAO). Compared with PBS-treated controls, h-iSC tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…We found that MSC transplantation activated endogenous iNSPCs around the grafted sites. Similar to these findings, we recently showed that h-iSC transplantation activated endogenous iNSPCs around the grafted sites but not NSPCs in the SVZ [21]. These findings suggest that although the precise traits of endogenous iNSPCs activated by MSC transplantation remain unclear, not only h-iSCs but also h-MSCs activate locally derived endogenous NSPCs, rather than SVZ-derived NSPCs, after cell transplantation.…”
Section: Discussionsupporting
confidence: 81%
“…We found that MSC transplantation activated endogenous iNSPCs around the grafted sites. Similar to these findings, we recently showed that h-iSC transplantation activated endogenous iNSPCs around the grafted sites but not NSPCs in the SVZ [21]. These findings suggest that although the precise traits of endogenous iNSPCs activated by MSC transplantation remain unclear, not only h-iSCs but also h-MSCs activate locally derived endogenous NSPCs, rather than SVZ-derived NSPCs, after cell transplantation.…”
Section: Discussionsupporting
confidence: 81%
“…Nuclei were counterstained with DAPI (1:500), and fluorescence images were captured using a laser scanning microscope (LSM780). The number of nestin + iNSPCs (nestin + /mCherry − cells) or Sox2 + iNSPCs (Sox2 + /mCherry − cells) was compared between iNSPC monocultures (control) and iNSPCs cocultured with mCherry + MGs/MΦs using 12 data points (4 areas/sample, 3 samples/marker), as described [ 13 ]. Additionally, the ratio of Ki67 + iNSPCs (Ki67 + /mCherry − cells) to all iNSPCs (DAPI + /mCherry − ) cells was compared between iNSPC monocultures and iNSPCs cocultured with mCherry + MGs/MΦs using 12 data points (4 areas/sample, 3 samples/marker), as described [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Control GFP + iNSPC monocultures and GFP + iNSPCs cocultured with MGs/MΦs were collected by FACS. Next, total RNA isolated from cells with the RNeasy Micro Kit (Qiagen, Hilden, Germany) was used in microarray analysis, as described [ 2 , 6 , 13 ]. The microarray data were analyzed using the Affymetrix Transcriptome Analysis Console [ 2 , 6 , 13 ] and Metascape gene ontology (GO) tool [ 14 ], as described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the risk of tumor formation, the safety profile of iPSC-derived cell sources has been recently improved using genetic safety switch systems 22,23 . Previous studies showed that transplantation of iPSC-derived NPCs can release neurotrophic factors, form new connections within the damaged neural circuits 9,24 and repair functional deficits in stroke animals 25,26,10,8,7,27 .…”
Section: Introductionmentioning
confidence: 99%